The Quality of Nugget of Broiler Chicken Meat with Addition of Sago Flour (Metroxylon Sp.) - Sitti Nurlela; H. Hastuti; S. Suparman (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2018)
This study aims to determine the quality of broiler chicken nuggets with the addition of sago flour (Metroxylon Sp.) As a binder. This study used a completely randomized design (CRD), with a factorial pattern of 3 x 3 and 3 replications where factor A was broiler chicken meat (A1 = 60%, A2 = 70% and A3 = 80%) and factor B was sago flour (B1 = 30%, B2 = 20% and B3 = 10%). The material used was 4.5 kg of fresh meat broiler chicken and 900 g of sago flour. Based on the results of the study showed that the administration of sago flour as a binder in broiler chicken nuggets dough did not significantly affect (P 0.05) the quality of broiler chicken nuggets. The conclusion of the study showed that the administration of sago flour to the quality of broiler chicken nuggets had no real effect